"I've been cheated, been mistreated, when will I be loved": Two decades of infidelity research through an intersectional lens. (March 2023) - Weiser, Dana A; Shrout, M Rosie; Thomas, Adam V; Edwards, Adrienne L; Pickens, Jaclyn Cravens
Infidelity is a common experience within romantic relationships and is closely linked with relationship dissolution and well-being. Using an intersectionality theoretical framework, we undertook a systematic review of the infidelity literature in flagship journals associated with the disciplines of the International Association for Relationship Research. Our review includes findings from 162 published empirical articles. We identified several themes within the infidelity literature, including: individual, interpersonal, and contextual predictors; outcomes and reactions; beliefs and attitudes; prevalence; and conceptualization. We also found that the infidelity literature primarily utilizes participants who are White, heterosexual, cisgender individuals who reside in the United States or Canada. Moreover, researchers were limited in information they provided about participants' identities so in most articles it was difficult to assess many dimensions of identity. Ultimately, these findings limit our ability to apply an intersectional framework. We argue that researchers should extend the research they cite, collect richer demographic data, expand their samples (especially beyond White heterosexual cisgender American college students), and consider the sociohistorical context of their participants (e.g., the particular social circumstances and historical forces which shape individuals' lived experiences). For example, scholars using an intersectional framework would explain their participants' relationship experiences through a lens which includes systems of sexism, racism, heterosexism, cissexism, classism, etc., in conjunction with individual and interpersonal factors.